A simple drop‐and‐detect method using porous alumina ceramics as platforms for rapid surface‐enhanced Raman spectroscopy. (1st August 2016) - Lou, Xiutao; Zhao, Xiaorong; Lin, Xiang; Zhang, Meiling; Xu, Lianjie; Wang, Haoruo; Hasi, Wuliji; Lu, Zhiwei
Abstract : We propose a simple and rapid surface‐enhanced Raman spectroscopy (SERS) method based on the dropping and detection of a sample droplet on a porous alumina ceramic platform (ACP). The SERS versatility of the proposed drop‐and‐detect method was demonstrated by using well‐studied water‐soluble melamine and ethanol‐soluble 4‐mercaptobenzoic acid as Raman probes. Colloidal silver nanoparticles were used as SERS substrates. Because of the fast permeation of the sample droplet by using ACPs, reproducible SERS measurements could be performed within a minute after the dropping of the sample solution. In comparison with its counterpart quartz plate, the cost‐effective ACP made the uniformity of the distribution pattern of the dried droplet improved by an order of magnitude. The measurement sensitivity was also greatly improved by using ACPs due to their enrichment functions. The lowest detectable concentrations achieved for melamine and 4‐mercaptobenzoic acid were 2.5 µg/l and 2.5 × 10 −8 mol/l, respectively. The proposed drop‐and‐detect method was also demonstrated by quantitative detection of trace level melamine in liquid milk achieving a lowest detectable concentration of 0.1 mg/l, indicating its advantages of simplicity and efficiency for practical SERS applications. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A simple and rapid surface‐enhanced Raman spectroscopy method based on a porous alumina ceramic platform has been demonstrated. Reproducible surface‐enhanced Raman spectroscopy measurements could be performed within a minute after the dropping of the sample solution. In comparison with its counterpart quartz plate, the cost‐effective alumina ceramic platform was found to be capable of significantly improving the measurement speed, sensitivity and reproducibility.